Urban lives an industrial city and its people during the twentieth century - Dribe, Martin 1968-; Nilsson, Therese 1977-; Tegunov, Dmitry 1988- (Oxford University Press, 2024)
"This chapter introduces the research presented in the book. It starts by highlighting the importance of an individual-level perspective to understand how long-term economic and societal changes connected with industrialization and post-industrialization have affected individuals and families during the twentieth century and into the twenty-first. It discusses a detailed periodization, linking the developments in Landskrona to broader economic and societal developments in Sweden and internationally. The chapter also presents the study area and the Scanian Economic-Demographic Database and discusses the core concepts, variables, and methods used in the different chapters of the book"--
Keywords: Geschichte 1900-2000; Wirtschaftsentwicklung; Verstädterung; Sozialer Wandel; Schweden; Landskrona; Landskrona (Sweden) / Economic conditions; Landskrona (Sweden) / Social conditions; Urbanization / Sweden; Industrialization / Sweden; Urbanisation / Suède; Industrialisation / Suède; Aufsatzsammlung